2014
DOI: 10.1002/2014gl059251
|View full text |Cite
|
Sign up to set email alerts
|

New permafrost is forming around shrinking Arctic lakes, but will it last?

Abstract: Widespread lake shrinkage in cold regions has been linked to climate warming and permafrost thaw. Permafrost aggradation, however, has been observed within the margins of recently receded lakes, in seeming contradiction of climate warming. Here permafrost aggradation dynamics are examined at Twelvemile Lake, a retreating lake in interior Alaska. Observations reveal patches of recently formed permafrost within the dried lake margin, colocated with discrete bands of willow shrub. We test ecological succession, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 32 publications
1
47
1
Order By: Relevance
“…The soil heat flux, on the other hand, depended strongly on soil thermal properties. This is in contrast to the studies by Blok et al (2010) and Briggs et al (2014), which identified soil shading as important control of local permafrost thaw. A schematic of the differences we found between key components of the dwarf shrub and wet sedge system can be found in Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…The soil heat flux, on the other hand, depended strongly on soil thermal properties. This is in contrast to the studies by Blok et al (2010) and Briggs et al (2014), which identified soil shading as important control of local permafrost thaw. A schematic of the differences we found between key components of the dwarf shrub and wet sedge system can be found in Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Lastly there is the challenge of quantifying “hot spots and moments” and “effective discharge” for biogeochemical processing of nutrients and organic matter in watersheds to understand river corridor functions and [e.g., McClain et al ., ; Doyle et al ., ]. We review the history and progress in these and other river corridor concepts and we also review the tried and true field practices with a view toward emerging techniques such as novel applications of geophysical techniques [ Briggs et al ., ; Lowry et al ., ], thermal imaging [e.g., Dugdale et al ., ; Briggs et al ., b], and satellite observations [e.g., Alsdorf et al ., ; Townsend and Foster , ]. Practical examples relating to management of river corridors are considered, such as concepts to quantify and characterize the chemical reactions of major concern and their relation to practical aspects of the conjunctive management of surface and groundwater management (e.g., bank filtration).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these change studies [1,30,31] quantify change between two distinct time periods and focus on either a few distinct lakes or the overall regional change. This methodology works reasonably well for mapping forest extent or urban growth that are distinct and comparatively stable, but is less effective with water because water bodies are highly dynamic both inter-annually and seasonally.…”
Section: Introductionmentioning
confidence: 99%